GPS- Finger Print System - Murali, K; Gowda, Adarsh (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2019)
The biometric sensors are highly secured (example: FINGERPRINT RETINA SCANNERS, HEARTBEAT, SWEAT, SOUND PATTERN, and FACE ID). Most of the security system widely use FINGERPRINT based systems only .GPS software system is also one of the security system for military purpose. Many secret data transfer through this GPS line .By developing an application of GPS FINGERPRINT SYSTEM we can improve highly secured data .This GPS FINGERPRINT SYSTEM works on the basis of fetching GPS location and FINGERPRINT access , it means that whenever the FINGERPRINT is accessed in our system it can also fetch the information of that person with the present location . Many applications can be built under this system, example: banking data security, police tracking, hospital treatment, military, transaction.